One stage surgical treatment of aortic valve disease and aortic coarctation with aortic bypass grafting through the diaphragm and aortic valve replacement. Issue 1 (December 2015) - Yu, Zipu; Wu, Shengjun; Li, Chengchen; Zou, Yu; Ma, Liang
Abstract Objectives To validate ascending aorta-lower abdominal aorta bypass grafting treatment for patients with descending aortic coarctation and an aortic valve disease. Methods The three patients in whom a descending atypical aortic coarctation was associated with an aortic valve disease were treated with one stage surgical treatment with aortic bypass grafting through the diaphragm and aortic valve replacement in our heart center. Operative technique consisted of performing ascending aorta-lower abdominal aorta bypass grafting through diaphragm muscle and implementing aortic valve replacement. The mean time for extracorporeal circulation and occluding clamp of aorta was recorded. Blood pressure data for pre- and post-operation was measured in the limbs. Computer-enhanced transvenous angiograms of pre- and post-operation were applied for detection of aortic stenosis. The other adverse events were noticed in outpatient service during a follow-up period. Results The mean extracorporeal circulation time was 54 ± 11 min. The mean time for occluding clamp of aorta was 34 ± 6 min. An arterial pressure gradient was totally corrected after surgical treatment. Post-operation computer-enhanced transvenous angiograms showed the grafts to be open with a fluent flow. The patients had no gastrointestinal tract complications. No adverse event was noticed during a follow-up period in outpatient service. Conclusions Treatment of ascending aorta-lower abdominal aorta bypass is advisable for patients with descending aortic coarctation and an aortic valve disease.